A new HLA‐A*26 family allele – HLA‐A*26:103. Issue 6 (10th March 2015) - Street, J.; Climer, T.; Johnson, J.; Pepperall, J.; Darke, C.
<x xml:space="preserve">Abstract</x> HLA‐A*26:103 differs from A*26:01:01 by one base (559C>G) in exon 3 resulting in an amino acid substitution of R163G.